Co-assembly of graphene/polyoxometalate films for highly electrocatalytic and sensing hydroperoxide - Bao, Yayan; Chen, Zezhong; Wang, Yuzhen; Liu, Lizhen; Wang, Haiyan; Li, Zuopeng; Feng, Feng (Frontiers in Chemistry, 2023)
Graphene oxide (GO) films mixed with polyethylenimine (PEI) were prepared using a layer by layer assembly (LBL) method in which the GO component is then converted to reduced GO (rGO) in situ through an electron transfer interaction of a polyoxometalate (POM) that is assembled on the outer surface. With this, the devices by spreading composite films (PEI/rGO)n-POM with different numbers of PEI/rGO layer on ITO substrates were manufactured. The cyclic voltammetry (CV) reveals that the catalytic activity for H2O2 of (PEI/rGO)n-POM films was significantly higher than similar films (PEI/GO)n/PEI/POM manufactured by LBL with the same layers, although the catalyst POM content of (PEI/rGO)n-POM was only half that of (PEI/GO)n/PEI/POM. The catalytic activity of (PEI/rGO)n-POM films first increases and then decreases with an increasing number of PEI/rGO layer. The result shows that (PEI/rGO)3-POM films with three PEI/rGO layers exhibit the highest efficiency. Amperometric measurements of the (PEI/rGO)3-POM films exhibited improved current response, high sensitivity, wide linear range, low detection limit, and fast response for H2O2 detection. The enhanced catalytic property of (PEI/rGO)n-POM films is attributed to the electron transfer interaction and electrostatic interaction between POM and rGO.